2017
DOI: 10.3389/fmicb.2017.00725
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Biology Needs Wild Microbiomes

Abstract: The microbiome is a vital component to the evolution of a host and much of what we know about the microbiome derives from studies on humans and captive animals. But captivity alters the microbiome and mammals have unique biological adaptations that affect their microbiomes (e.g., milk). Birds represent over 30% of known tetrapod diversity and possess their own suite of adaptations relevant to the microbiome. In a previous study, we showed that 59 species of birds displayed immense variation in their microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
205
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(210 citation statements)
references
References 104 publications
3
205
2
Order By: Relevance
“…Similar to the gut microbiotas of cowbirds (Hird et al, 2014), vultures (Roggenbuck et al, 2014), and penguins (Dewar et al, 2014), great hornbills also contained a relatively high abundance of Fusobacteria. The relatively high abundance of Fusobacteria in great hornbills resulted from the genus Fusobacterium, and it may be related to many physiological functions of gut (Hird, 2017). Actinobacterium is an abundant phylum in the gut microbiota of toucans, and studies have shown a positive correlation of actinobacteria with fiber intake in humans (Lee, Rusch, Stewart, Mattila, & Newton, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the gut microbiotas of cowbirds (Hird et al, 2014), vultures (Roggenbuck et al, 2014), and penguins (Dewar et al, 2014), great hornbills also contained a relatively high abundance of Fusobacteria. The relatively high abundance of Fusobacteria in great hornbills resulted from the genus Fusobacterium, and it may be related to many physiological functions of gut (Hird, 2017). Actinobacterium is an abundant phylum in the gut microbiota of toucans, and studies have shown a positive correlation of actinobacteria with fiber intake in humans (Lee, Rusch, Stewart, Mattila, & Newton, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquity, high diversity and function of host-associated microbes is changing our understanding about animal biology (McFall-Ngai et al, 2013;Hird, 2017). This is due, in part, to the pivotal role that host-associated microbial communities can play in different aspects of host life history, overall host health, and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…We conclude by considering how this study links to the call for greater research effort on microbiomes in natural populations of animals and plants (Hird, 2017;Perez-Jaramillo, Carrion, Hollander, & Raaijmakers, 2018). The tight environmental controls and simplifying conditions of laboratory studies facilitate the study of fundamental mechanisms, but there is increasing evidence that some important processes and interactions are not displayed under laboratory conditions Ericsson et al, 2017).…”
Section: Insights Into Microbiomes Of Wild Animalsmentioning
confidence: 84%